Teacher's Need in the Continuing Professional Development Program for Teachers of Vocational High School throughout Surakarta Residency - Murwaningsih, Tri; Sawiji, Hery; Murtini, Wiedy; Akbarini, Nur Rahmi (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
This research aimed to identify the activities needed by teachers in holding the Continuing Professional Development Program. This research employed survey type of non-experimental quantitative research method. This type of research was used when the author wants to find out the population's opinion by conducting a study on the sample of population. The population of research consisted of all teachers of Vocational High School in Business and Management field in Surakarta City Residency. The sampling technique used was purposive sampling. Techniques of collecting data were observation, interview, documentation, and questionnaire. Quantitative data obtained was the one processed using Microsoft Excel with the scale specified by the author, while qualitative data was analyzed using triangulation technique. The result of research showed that Program Continuing Professional Development had been conducted despite different proportion for self-development, scientific publication, and innovative work. Thus, the appropriate strategy was required to solve some problems encountered by teachers